2022
DOI: 10.3390/ijms231911028
|View full text |Cite
|
Sign up to set email alerts
|

GSTT1/GSTM1 Genotype and Anti-Tuberculosis Drug-Induced Hepatotoxicity in Peruvian Patients

Abstract: In Peru, 24,581 people were diagnosed with tuberculosis (TB) in 2020. Although TB treatments are effective, 3.4–13% are associated with significant adverse drug reactions (ADRs), with drug-induced liver injury (DILI) considered the most predominant. Among the first-line antituberculosis drugs, isoniazid (INH) is the main drug responsible for the appearance of DILI. In the liver, INH is metabolized by the enzymes N-acetyltransferase-2 (NAT2), cytochrome P450 2E1 (CYP2E1), and glutathione S-transferase (GST) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…This allowed us to evaluate the effects of migration over thousands of years as well as helping differentiate populations based on evolutionary bottlenecks, revealing a distinct genetic fingerprint on the Americans' ancestors 22 . Moreover, we have found that the degree of ancestry (mestizos vs natives) and the geographic altitude habitat (high vs low landers) are linked 23 .…”
Section: Initial Findings and Key Contributions For Genomic Medicine ...mentioning
confidence: 87%
See 1 more Smart Citation
“…This allowed us to evaluate the effects of migration over thousands of years as well as helping differentiate populations based on evolutionary bottlenecks, revealing a distinct genetic fingerprint on the Americans' ancestors 22 . Moreover, we have found that the degree of ancestry (mestizos vs natives) and the geographic altitude habitat (high vs low landers) are linked 23 .…”
Section: Initial Findings and Key Contributions For Genomic Medicine ...mentioning
confidence: 87%
“…Our initial results point to greater hepatotoxicity in antiretroviral cotreatment on the coast. Thus, by considering the genetic diversity within and between populations, healthcare providers are beginning to better predict adverse drug reactions, adjust dosages, and select the most appropriate medication, thereby enhancing patient safety and treatment efficacy 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…These first-line medications are documented to induce mild to severe liver injury leading to the discontinuance of treatment that give rise to drug resistance and a cure not being achieved. 7 For instance, RIF causes thrombocytopenia, pain, nausea, and hepatitis in combination with other drugs; PZA leads to oxidative stress, arthralgia, and hepatitis through the 5-hydroxypyrazinoic acid; neuritis and color blindness are linked to ethambutol toxicity; while ethionamide leads to diarrhea and hepatotoxicity. 8, 9 Collectively, these ATDs elicit toxic metabolites, free radicals and reactive oxygen species (ROS) to become the main cause of injury to the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Esto implicaría que la isoniacida sería una de las drogas hepatotóxicas y su concentración debería disminuirse en aquellos pacientes que presenten el polimorfismo de acetilador lento; de otro lado, la dosis de rifampicina debería incrementarse para disminuir el riesgo de monoresistencia (6) . La asociación entre el genotipo y el desarrollo de hepatotoxicidad ha sido reportado (7) . Después de la infección por M. tuberculosis no todos desarrollamos la enfermedad y una de las causas estaría relacionada con el cromosoma 3q23 (8) .…”
unclassified